Pediatric Oculoplastic Surgery (Springer International Publishing, 2018)
This well-illustrated book presents the latest diagnostic concepts and management techniques in the rapidly expanding subspecialty of pediatric oculofacial plastic surgery. Covering all aspects of the field and taking into account numerous surgical innovations and exciting new medical treatment concepts that have emerged since publication of the previous edition in 2002, Pediatric Oculoplastic Surgery, 2nd Edition will prove to be an invaluable resource for both the comprehensive ophthalmologist and the subspecialist with a particular interest in pediatric disorders of the eyelids, orbit, and nasolacrimal system. Topics discussed, in addition to clearly illustrated basic oculoplastic procedures, include surgical innovations ranging from the Sonopet system for safer removal of bone in lacrimal surgery to the development of complex image guidance technology for sinus and orbital surgery. Detailed discussion of syndromic and non-syndromic congenital anomalies explore a variety of surgical techniques and the nuances of applying these approaches in the management of various structural abnormalites. Further important advances include new analytic laboratory techniques, which can illuminate the genetic basis of many pediatric oculoplastic disorders, various medical management advances such as the role of beta blockers in the treatment of facial and orbital hemangiomas, and the development of biologic pathway blockers inhibiting tumor growth which offer real potential for reducing the necessity of surgical intervention. .